ASSESSMENT OF FUEL MOVEMENT IN COMBUSTION PROCESS BASED ON THE DIGITAL IMAGE - Pater, Łukasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The article refers to the method of indicating the type of movement by means the digital image processing and analysis on the example of a coal dust movement sequence. Presented approach is broaden the perspective of use the vision systems in the combustion processes control, thus increasing their effectiveness. The results showed a correct reflection of the real fuel movement in the discrete surface of the vector fields using the optical flow method. Including a numerical method for vector field analysis allowed to indicate six types of movement. Research, covering a fragment of the studied phenomenon, exhaust all cases of assessing the fuel particles displacement.